PENGARUH DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT. ANUGRAH NIAGA JAYA CABANG PEKANBARU - Hendrayani, Hendrayani (Eko dan Bisnis: Riau Economic and Business Review, 2020)
Research conducted at PT. Grace Niaga Jaya Branch Pekanbaru . Based on research background mentioned above, the writer can formulate the problem in this study is Are in siplin work take effect to performance employees at PT. Grace Niaga Jaya Branch Pekanbaru . The purpose of this study is to knowing influence discipline to performance employees Â  on PT. Grace Niaga Jaya Branch Pekanbaru .Data analysis in this research is done by using method descriptive Â  and quantitative .Method descriptive that is data analysis with way decomposition theories contained in list library and connected with the data obtained from results research that will be collected , grouped and tabulated then taken conclusion . And methods quantitative with technique simple linear regression . Samples taken in research this is numbered 44 people, h a sil research is seen from calculation could obtained equation regression simple linear as the following : Y = 15.324 + 0.659X that there is a significant influence variable discipline to performance that is could seen value t_hitung (5471)> t_tabel (2.0180), the value coefficient determination ( R Square) of 0.416 ie that magnitude influence variable free to variable bound by 41.6 percent sedangka the rest by 58.4 percent affected by variable others